Altered grey matter volume and cortical thickness in patients with schizo-obsessive comorbidity. (30th June 2018) - Wang, Yong-ming; Zou, Lai-quan; Xie, Wen-lan; Yang, Zhuo-ya; Zhu, Xiong-zhao; Cheung, Eric F.C.; Sørensen, Thomas Alrik; Møller, Arne; Chan, Raymond C.K.
Highlights: We examined grey matter (GM) volume in patients with schizo-obsessive comorbidity (SOC), schizophrenia (SCZ), obsessive-compulsive disorder (OCD) and healthy controls. Decreased GM volume of the medial orbital frontal gyrus, the medial superior frontal gyrus, the rectus gyrus, the anterior cingulate cortex, the left thalamus and the left cerebellum were found in patients with SOC compared with controls. Decreased cortical thickness of the right superior temporal gyrus, the right angular gyrus, the right supplementary motor area, the right middle cingulate cortex and the right middle occipital gyrus were found in patients with SOC compared with controls. These findings highlight the grey matter changes specific to patients with SOC. Abstract: Recent findings suggest that schizo-obsessive comorbidity (SOC) may be a unique diagnostic entity. We examined grey matter (GM) volume and cortical thickness in 22 patients with SOC, and compared them with 21 schizophrenia (SCZ) patients, 22 obsessive-compulsive disorder (OCD) patients and 22 healthy controls (HCs). We found that patients with SOC exhibited reduced GM volume in the left thalamus, the left inferior semi-lunar lobule of the cerebellum, the bilateral medial orbitofrontal cortex (medial oFC), the medial superior frontal gyrus (medial sFG), the rectus gyrus and the anterior cingulate cortex (aCC) compared with HCs. Patients with SOC also exhibited reduced cortical thickness in the right superior temporal gyrus (sTG), the right angular gyrus, the right supplementary motor area (SMA), the right middle cingulate cortex (mCC) and the right middle occipital gyrus (mOG) compared with HCs. Together with the differences in GM volume and cortical thickness between patients with SOC and patients with only SCZ or only OCD, these findings highlight the GM changes specific to patients with SOC.